Evaluasi Manajemen Usaha Sate Maranggi Bang Bahin Di Wilayah Plered Purwakarta - Rhiswandi, Rhandi; Mubarok , Ibnul; Suhendra , M. Fahat; Subroto , M. Alvin (Tractare: Jurnal Ekonomi-Manajemen, 2025)
Sate Maranggi MSMEs "Bang Bahin" is one of the traditional culinary businesses that is developing in Plered District, Purwakarta. This research aims to analyze the operational processes, business obstacles, and development strategies applied by owners in maintaining business sustainability. The research method used direct observation, in-depth interviews with business owners, and field documentation. The results of the study show that businesses face several main obstacles, such as limited capital, fluctuations in meat prices that affect profit margins, and uncertain weather conditions that interfere with the satay-burning process. In addition, all operational activities are carried out by the owner himself because there are no employees, so that production capacity is limited and the service time becomes longer when there is an increase in the number of buyers. Even so, these MSMEs still have advantages through the distinctive taste of satay, affordable prices, strategic locations, and customer loyalty formed from friendly service. This study concludes that development strategies that can be implemented include improving financial management, diversifying meat suppliers, improving business facilities, and utilizing digital media as a means of promotion. This finding is expected to be a reference for culinary MSME actors in facing operational challenges and increasing business competitiveness.